2022
DOI: 10.3389/fendo.2022.933635
|View full text |Cite
|
Sign up to set email alerts
|

Integrated bioinformatic analysis reveals immune molecular markers and potential drugs for diabetic cardiomyopathy

Abstract: Diabetic cardiomyopathy (DCM) is a pathophysiological condition induced by diabetes mellitus that often causes heart failure (HF). However, their mechanistic relationships remain unclear. This study aimed to identify immune gene signatures and molecular mechanisms of DCM. Microarray data from the Gene Expression Omnibus (GEO) database from patients with DCM were subjected to weighted gene co-expression network analysis (WGCNA) identify co-expression modules. Core expression modules were intersected with the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Problems in Nf-kB1 activation have been linked to numerous inflammatory diseases, while continuous inhibition affects immune cell development or delayed cell growth [ 12 ]. It is widely used as a therapeutic target in diabetic cardiomyopathy [ 13 ]. Thus, inhibition of the Nf-kB1 helps to reduce the anti-inflammatory activity of targeting Nf-kB1 in the associated pathways [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Problems in Nf-kB1 activation have been linked to numerous inflammatory diseases, while continuous inhibition affects immune cell development or delayed cell growth [ 12 ]. It is widely used as a therapeutic target in diabetic cardiomyopathy [ 13 ]. Thus, inhibition of the Nf-kB1 helps to reduce the anti-inflammatory activity of targeting Nf-kB1 in the associated pathways [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between metabolic status and immunological state is complex and tightly intertwined [45]. Diabetes mellitus, is a metabolic disease, exerts profound effects on immune responses and substrate energy metabolism [46][47][48]. In diabetes, both innate and adaptive immune responses are profoundly affected, particularly in the context of DCM, where in ammation-related tissue injury triggers activation of immune responses in the heart [45].…”
Section: Discussionmentioning
confidence: 99%
“…Some experimental results have demonstrated the mRNA or protein expression levels of the seven genes. Among the identified seven up-regulated genes, researches have shown that the levels of DUOX2, CXCL10 and CD40LG expression were significantly higher in patients with DCM 32 , 74 , 75 , and ESR1 and COL1A1 were substantially up-regulated in the mouse model of DCM 22 , 76 . In addition, the expression levels of CXCL11 and OLR1 have been proved to be elevated in heart failure patients 77 , 78 .…”
Section: Discussionmentioning
confidence: 99%